Differential expression of HIF1A and its downstream target VEGFA in the main subtypes of renal cell carcinoma and their impact on patient survival - Strikic, Ante; Kokeza, Josipa; Ogorevc, Marin; Kelam, Nela; Vukoja, Martina; Dolonga, Petar; Tomas, Sandra Zekic (Frontiers in Oncology, 2023)
Renal cell carcinoma (RCC) represents around 3% of all cancers, with the most frequent histological types being clear-cell RCC (ccRCC), followed by papillary (pRCC) and chromophobe (chRCC). Hypoxia-inducible factors (HIFs), which promote the expression of various target genes, including vascular endothelial growth factor (VEGF) and the high-affinity glucose transporter 1, have an important role in the pathogenesis of RCC. This study investigated the immunohistochemical expression of HIF-1α and VEGF-A, showing significantly higher HIF-1α nuclear expression in pRCC compared to ccRCC, while there was no significant difference in VEGF-A protein expression between the analyzed histological RCC subtypes. The quantitative reverse transcription polymerase chain reaction for HIF1A showed no statistical difference between histological types. Data from publicly available RNA sequencing databases were analyzed and showed that, compared to healthy kidney tissue, VEGFA was significantly up-regulated in ccRCC and significantly down-regulated in pRCC. The comparison between histological subtypes of RCC revealed that VEGFA was significantly up-regulated in ccRCC compared to both pRCC and chRCC. There was no statistically significant difference in survival time between HIF1A high- and low-expression groups of patients. As for VEGFA expression, pRCC patients with low expression had a significantly higher survival rate compared to patients with high VEGFA expression.